(untitled) (Orfeu, 2020)
This work introduces the idea of compositional analysis, as an alternative, for the research area in musical composition, to the traditional analytical approaches, of an essentially musicological nature. To do so, I present an analysis of my piece for solo guitar, entitled Répéter, which, by means of collecting and reflecting upon a series of data, impressions, materials and diverse records of the compositional process, illustrates a possible path for the analytical practice, in the area. Before presenting it, however, I briefly comment on the bases of this approach, through: 1) an introductory discussion about the academic and artistic contexts that justify the proposal; and 2) a conceptual approach to compositional analysis based on the ideas of lines, place, meshwork and compositionality by Deleuze and Guattari (1995), Tim Ingold (2008, 2011, 2012) and Paulo Costa Lima (2012), respectively. Therefore, I hope to launch an experimental analytical horizon, which is rather an extension of the creative process itself, instead of a search for representation or explanation of the work, as a product of that very process.